Implementasi Kebijakan Pemerintah Kabupaten Mandailing Natal Mengenai Pemberian Dana Insentif Guru Agama - Desi Rani; sudarman sudarman (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
This devotion realized in Mandailing Natal District regarding the Provision of Incentive Funds for Religious Teachers through Edward III's theory, namely communication, resources, disposition and bureaucratic structure. The implementation of this devotion consists to two stages: The initial stage of the research, to find out a complete figure of the implementation for previous activities in order to put the right formulation for the next implementation plan. The study used a qualitative method involving 5 informants from teachers in Mdta, Tpa, and Pontren selected by purposive sampling technique, using two types of data, primary and secondary data. The second stage of implementation/application, after the research conclution analyzed, then the author determines the right formulation for program implementation, refers to Edward III's theory. After coordinated to policy makers, then authors and other parties agreed to implement the program using Edward III's theory. Based on the results of the implementation that has been applied regarding the Provision of Religious Teacher Incentive Funds through the approach of 4 aspects refers to Edward III's theory, then it shows that the implementation of the Mandailing Natal Regency government's policy regarding the Incentive Fund giving for Religious Teachers has not been implemented well before, then after the implemented of these 4 aspects, the situation in implementing the policy has improved and tends to improve, although there are still some things that become obstacles, such as the implementation of open dispositions that are still a bit fully reluctant implemented.